Assessing the Risk Factors for Metabolic Syndrome in Adult Patients with Sickle Cell Anemia in Jazan Region, Kingdom of Saudi Arabia - Abdalla, Saif Elden B.; Alhassen, Muntaser Mohammed Fadoul; Alam, Mohammed Shane; Mustafa, Sarra Kamal; Almaki, Mohamed Mubark; Abdelrahman, Mohamed H. (Disease and Health: Research Developments Vol. 8, 2025)
Hematological anemia is a characteristic of the hereditary condition known as sickle cell disease (SCD). SCD is considered the world's most prevalent and widespread hemoglobinopathy. According to several studies, adults with sickle cell disease may exhibit metabolic syndrome symptoms such as hyperglycemia, hypertension, and dyslipidemia. This study's objective was intended to assess the steady-state risk variables for metabolic syndrome in adults with sickle cell anemia in the Jazan region. A case-control research with 35 adult sickle cell disease patients and 35 healthy controls was carried out. The study was conducted in the Jazan area in the period of 2021 to 2022. The population was Saudi patients with sickle cell anemia as a test group and healthy volunteers as a control test. The National Cholesterol Education Program - Adult Treatment Panel III (NCEP-ATPIII) was used to diagnose metabolic syndrome after the data were examined to determine fasting plasma glucose, lipid profile, and uric acid. Mean, standard deviation (SD), and p-value were used to express the data. In order to establish statistical significance, a value of 0.05 was employed. Fasting triglyceride levels were comparable between patient and control groups (P-value = 0.54), high-density lipoprotein cholesterol (HDL-C) was significantly low in the case group compared to the control group (P-value = 0.03) and the uric acid level was significantly different in patient and control groups (P-value = 0.55). There was significant decrease in HDL-C and FPG among SCD patients compared to the control group while no significant difference in fasting triglyceride and uric acid between patients and control groups. Focusing on the development of metabolic syndrome in SCA patients may provide new insights for therapeutic strategies with the aim of reducing mortality and morbidity.